2011
DOI: 10.3390/ijerph8051503
|View full text |Cite
|
Sign up to set email alerts
|

Does Secondhand Smoke Affect the Development of Dental Caries in Children? A Systematic Review

Abstract: This review evaluated evidence of the relationship between secondhand smoke (SHS) and dental caries in children in epidemiological studies. Relevant literature was searched and screened, and the methodological quality was assessed. The search yielded 42 citations. High-quality studies including one cohort format and 14 case-control format studies were selected. Early childhood caries was examined in 11 studies. The independent association of SHS was significant in 10 studies, and the strength was mostly weak t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 47 publications
1
58
0
1
Order By: Relevance
“…Clinical studies have shown a positive correlation between smoking and periodontal disease (Bergstrom, 2014; Borojevic, 2012; Smejkalova et al, 2012) and caries rates (Aguilar‐Zinser et al, 2007; Voelker et al, 2013), although these links are also considered to be inconclusive (U.S. Department of Health and Human Services, 2014). Additional lifestyle factors that are often socioeconomic in nature, including different eating habits and oral hygiene maintenance, have also been shown to differ substantially between smokers (including secondhand smoking) and nonsmokers (Benedetti, Campus, Strohmenger, & Lingström, 2013; Hanioka, Ojima, Tanaka, & Yamamoto, 2011; Smejkalova et al, 2012). The pattern of tooth decay in smokers is influenced by the increased risk of periodontal disease and caries is more frequently observed at, and below, the gingival junction of the teeth (Bharateesh & Kokila, 2014; Rad, Kakoie, Brojeni, & Pourdamghan, 2010; Soetiarto, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown a positive correlation between smoking and periodontal disease (Bergstrom, 2014; Borojevic, 2012; Smejkalova et al, 2012) and caries rates (Aguilar‐Zinser et al, 2007; Voelker et al, 2013), although these links are also considered to be inconclusive (U.S. Department of Health and Human Services, 2014). Additional lifestyle factors that are often socioeconomic in nature, including different eating habits and oral hygiene maintenance, have also been shown to differ substantially between smokers (including secondhand smoking) and nonsmokers (Benedetti, Campus, Strohmenger, & Lingström, 2013; Hanioka, Ojima, Tanaka, & Yamamoto, 2011; Smejkalova et al, 2012). The pattern of tooth decay in smokers is influenced by the increased risk of periodontal disease and caries is more frequently observed at, and below, the gingival junction of the teeth (Bharateesh & Kokila, 2014; Rad, Kakoie, Brojeni, & Pourdamghan, 2010; Soetiarto, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Secondhand smoke exposure has been associated with impaired cognitive ability in children (Chen et al, 2013;US DHHS, 2006) as well as a plethora of other conditions that could contribute to in-creased lost school days, such as middle ear infections, wheezing, coughing, bronchitis, pneumonia, slow lung development, as well as dental caries (Hanioka et al, 2011;Levy et al, 2011;Slayton, 2012;Tanaka et al, 2009;US DHHS, 2006, 2014a, 2014b, 2014c, 2014d. Living with a smoker might also be a proxy for low socio-economic status since smoking prevalence rates are disproportionately higher among persons of low education or low annual household incomes (Centers for Disease Control and Prevention, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A possible effect of second hand smoke on the development of dental caries in children is not clearly established; a recently published scientific revision has failed to demonstrate a potential association of second hand smoke with caries, maybe due to the heterogeneity of the studies included (Hanioka et al, 2011).…”
Section: Dental Cariesmentioning
confidence: 99%